Selection of Automated Order Picking Systems - Automated Storage and Retrieval Systems within Contract Logistics - Döllinger, Achim; Larsson, Tove (My University, 2016)
Increasing demands on contract logistics providers have led to an increasing interest in warehouse automation. Warehouse automation is expected to result in improved efficiency and effectiveness. The warehouse activity typically in focus for automation is order picking as it accounts for the majority of operational costs. The purpose of this study is to provide a guideline for the selection of an automated order picking system. The automated order picking systems in focus of this thesis are eight different automated storage and retrieval systems, which reduce or eliminate the non-value adding travelling in the order picking process. The guideline was developed alongside a specific case of an order picking process in a warehouse in Norrköping operated by Kuehne + Nagel AB. In order to achieve the purpose relevant literature is presented, the current order picking process is analysed and a market research of four different suppliers, namely Constructor, Kardex Remstar, Swisslog and Weland Lagersystem, and their respective systems is conducted. The study results in a guideline for the selection of automated storage and retrieval systems and a recommendation towards KN. Factors relevant for the selection of an automated storage and retrieval system are identified and eight different systems are evaluated. The guideline can be transferred and applied to other contexts and can be considered as a valuable tool in the selection of an automated order picking system.
Keywords: Transport; Övrig industriell teknik och ekonomi; Transport; Other industrial engineering and economics